A discourse network analysis of UK newspaper coverage of the "sugar tax" debate before and after the announcement of the Soft Drinks Industry Levy - Christina H. Buckton; Gillian Fergie; Philip Leifeld; Shona Hilton (BMC, 2019)
Abstract Background On 6th April 2018, the UK Government introduced the Soft Drinks Industry Levy (SDIL) as a mechanism designed to address increasing prevalence of obesity and associated ill health by reducing sugar consumption. Given that the successful introduction of upstream food and nutrition policies is a highly political enterprise involving multiple interested parties, understanding the complex network of stakeholders seeking to influence such policy decisions is imperative. Methods Media content analysis was used to build a dataset of relevant newspaper articles, which were analysed to identify stakeholder agreement or disagreement with defined concept statements. We used discourse network analysis to produce visual representations of the network of stakeholders and coalitions evident in the debate as it was presented in UK newspapers, in the lead up to and following the announcement of the Soft Drinks Industry Levy in the UK, from May 2015 to November 2016. Results Coding identified 3883 statements made by 214 individuals from 176 organisations, relating to 47 concepts. Network visualisations revealed a complex network of stakeholders with clear sceptical and supportive coalitions. Industry stakeholders appeared less united in the network than anticipated, particularly before the SDIL announcement. Some key industry actors appeared in the supportive coalition, possibly due to the use of corporate social responsibility rhetoric. Jamie Oliver appeared as a dominant stakeholder, firmly embedded with public health advocates. Conclusion This study highlights the complexity of the network of stakeholders involved in the public debate on food policies such as sugar tax and the SDIL. Polarisation of stakeholders arose from differences in ideology, focus on a specific policy and statements about the weight of evidence. Vocal celebrity policy entrepreneurs may be instrumental in gaining public and policy makers' support for future upstream regulation to promote population health, to facilitate alignment around a clear ideology.